Readiness of Malaysian food-based logistics service providers for halal practices - Ahmad Tarmizi, Hazwani (2015)
Halal is a code to describe things or actions that permitted by Shariah (Islamic Law) and it should be performed to show an obligation towards Islamic faith basically towards foods ingredients. However, halal aspect is not only restricted for ingredients of foods products but includes anything related to the halal food. In a way to serve halalan toyibban products to end consumers, all parts in supply chain of halal products also should be conducted according to halal guidelines. Logistics services are one of the parts in supply chain and most of halal foods producers using logistics services from logistics service providers (LSPs). As halal foods demands increasing, logistics players should be ready towards emerging of halal market in order to ensure halal integrity along halal foods supply chain. In order to be ready to involve in halal market, improvements need to be done by LSPs to make sure the integrity of halalan toyibban of halal food products along the supply chain. few aspects need to be considered by LSPs in providing good halal logistics services due to few problems reported respected to logistics practices for halal products. Organization vision to change, knowledge on halal logistics, company’s profiles, past experience, organization resources and structure, assurance system, internal and external environments, employees acceptance, management support as well as halal logistics barriers are the important aspects with regard to halal logistics. In the light of halal logistics scenario, the general objective of this study was established in order to investigate the readiness factors among Malaysia’s food-based LSPs for halal practices. This study was conducted in most states in Peninsular Malaysia such as Selangor, Kuala Lumpur, Negeri Sembilan, Melaka, Johor, Perak, Penang, Kedah, and Pahang and census method was used to select targeted respondents. The sample of this study was 156 food-based LSPs from a total population of 350 logistics companies. Face-to-face interviews with the respondents were conducted using structured questionnaires consisting of 5-point Likert Scale statements which were designed to measure readiness towards halal logistics among food-based LSPs. Relevant analyses were carried out to achieve the specific objectives of this study such as descriptive analysis, mean score analysis, chi-square analysis, correlation analysis, factors analysis, and logistic regression. These analyses used to describe LSPs company’s profiles, to measure the level of knowledge among food-based LSPs, to identify correlation between LSPs readiness with level of knowledge, to identify factors that influence LSPs readiness towards halal practices and to investigate the relationships between dependent variable (readiness towards halal logistics) with few independent variables that influenced the readiness towards halal logistics. Generally, the finding of this study found that experienced complying with any assurance systems, locations, types of logistics activities, presence of Muslim workers, level of knowledge and barriers have significance relationships towards LSPs’ readiness towards halal practices. While company vision to change, Halal Assurance System, employees acceptance, external and internal environments of the organization and management support were the five factors that influenced readiness towards halal logistics by the LSPs. Meanwhile, presence of Muslim workers, knowledge on halal logistics, and experience in complying with any assurance system, were determined as the factors that mostly influenced readiness towards halal logistics. Since the result of this study clearly showed that important of knowledge on halal logistics, experienced with standard or assurance system and presence of Muslim workers have significant effect on LSPs readiness for halal practices, thus authorized agency should impose compulsory halal terms for food-based LSPs.